A Polymer Strategy toward High‐Performance Multifunctional Perovskite Optoelectronics: From Polymer Matrix to Device Applications. Issue 7 (3rd February 2023) - Qin, Jianfang; Chen, Yangjie; Guo, Xiaowei; Yang, Haiying; Qin, Yinglian; Yao, Chenzhong; lv, Baohua; Bai, Yiyan; Zhan, Yan
Abstract: Perovskites with superior photophysical properties and simple solution processing are widely applied in solar cells, light‐emitting diodes, photodetectors, and lasers. However, the target of high‐performance multifunctional perovskite optoelectronics is hampered by their intrinsic properties, such as the undesired crystallization rate, ease of ion migration, poor stability, and high brittleness. A perovskite–polymer matrix, including a perovskite–polymer composite and a polymer–perovskite–polymer heterostructure, is adopted to handle the above issues. This review starts with the categorized polymer addition methods and the relevant polymer distribution for a perovskite–polymer matrix. In addition, the high performance originating from the controlled crystallization, stress regulation, inhibited ion migration, defect passivation, reduced interfacial recombination, and multifunctions from the enhanced stability, mechanical robustness, self‐healing ability, controllable dimension, and novel optical properties are then summarized. Meanwhile, the working mechanisms of a perovskite–polymer matrix in perovskite optoelectronics are also discussed. Finally, promising guidelines and proposals are provided to promote the commercialization of high‐performance multifunctional perovskite optoelectronics. Abstract : Polymer strategy is crucial to high‐performance multifunctional perovskite optoelectronics. A perovskite–polymer matrix enables high performance by controlling crystallization, regulating stress, inhibiting ion migration, passivating defects, and reducing interfacial recombination. Meanwhile, multifunctions from enhanced stability, mechanical robustness, self‐healing ability, controllable dimension, and novel optical properties are also achieved.